Analysis of Straight Vegetable Oil (SVO) Spray Characteristics at End of Injection (EOI) - Abdullah, Adam; R., Mamat; Nur Atiqah, Ramlan; Yoshiyuki, Kidoguchi; Azran, Zafri (Engineering and Technology Publishing, 2012)
The depletion source and the increasing demand of fossil fuel have prompted scientists and researchers to search new alternative fuels for diesel engine. Biodiesel is seen a promising alternative fuel to reduce dependent on conventional diesel fuel. Advantages of biodiesel compared to petroleum-based diesel include high biodegradability, excellent lubricity, higher flash point, no sulfur content and produces less air pollutants. Although biodiesel has many advantages on the fuel properties, the fuel consumption rate or lower horsepower output are still need to be improved. This is due to the differences in fuel properties especially the kinematic viscosity between diesel fuel (GO), biodiesel fuel (BDF) and straight vegetable oil (SVO). In this study, the effect of kinematic viscosity of SVO on the spray behavior at End of Injection (EOI) were investigated. High kinematic viscosity of fuel highly affects the spray characteristics at EOI. In additional, high injection pressure and high kinematic viscosity of SVO apply resistance at nozzle inner hole caused needle lift cannot completely close the nozzle at EOI signal. At the EOI in which the combustion temperature inside chamber reduces promptly, many fuel droplets could not undergo a complete atomization process especially for large size of diameter fuel droplets. This phenomenon result the development of carbon deposition around the nozzle tip area and it will cover the nozzle hole. The development of carbon deposition will affect the fuel flow from nozzle. This study indicates that fuel injection pressure show no effect on SVO spray characteristics at the end of injection. Furthermore, high ambient temperature spray will reduce the kinematic viscosity value of SVO and could improve SVO spray atomization at end of injection.